Genetic divergence between the scad subspecies Trachurus Mediterraneus (Carangidae, pisces) from the Black Sea and the Mediterranean - DOBROVOLOV, I.S. (Mediterranean Marine Science, 2000)
Analysis of myogen and eleven enzymes (AAT, ADH, EST, GPI, IDHP, LDH, MDH, MEP, PGDH, PGM and SOD) were carried out by using starch gel and isoelectric focusing electrophoresis on thinlayer and ultrathin polyacrylamide ampholine and servalite gels in scad species from the Black Sea, the Sea of Marmara, the Aegean Sea, and the Mediterranean. Data from electrophoretic investigations was used to clarify the population structure of the scad migrating in the Bulgarian aquatory of the Black Sea and consisting of two main subpopulations: a) a "Black Sea" one hibernating in this sea only, and b) a "Sea of Marmara" one hibernating in that sea and contiguous Black Sea regions around the Bosporus. Non-specific muscular esterases were used, because they were appropriate for identification of both subspecies: Trachurus mediterraneus ponticus Aleev and Tr.m.mediterraneus Steindachner. Nei's genetic distance (D=0,0113) was used as an indication of their isolation dated back to the Carangate Period. An attempt was made to check the hypothesis of the origin of "large" ("giant") scad in the Black Sea as a result of the heterozygotic interbreeding between Tr.m.ponticus Aleev and Tr.m.mediterraneus Steindachner. A new allele Est-1E as well as the previously known alleles Est-1A and Est-1-B, were found in Mediterranean scad Tr.m.mediterraneus caught off Nice (France). It's proposed that the presence of the large form of large scat in this area is also a consequence of the heterozytic efect from the interbreeding between a population marked by Est-1-A and Est-1-B and a population marked by Est-1-E, probably inhabiting the waters around Gibraltar in the Atlantic Ocean.